MODEL PENGELOLAAN KEBERSIHAN KOTA MAKASSAR - Bau Asseng (JSSHA ADPERTISI JOURNAL, 2021)
Public sector activities still dominate solid waste management in Indonesia. Meanwhile, the capacity of the public sector is very limited in terms of time, cost, personnel and facilities and infrastructure for waste management. There are various efforts to encourage waste management both at the source of waste through the 3R concept, in management through waste banks, as well as in final waste disposal by involving the private sector, but it is not yet known which concept is the most effective in mapping waste to achieve zero waste. This study examines the constraints and prospects of each model and its implementation in the city of Makassar. The results of the study show that the collaboration model of the Household and the Waste Bank with 3 approaches, namely the independent participation pattern, the customer pattern, and the reward pattern, is the most effective model for reducing waste to zero waste.